2023
DOI: 10.1101/2023.10.18.562946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative analyses of disease-linked missense mutations in the RNA exosome modeled in budding yeast reveal distinct functional consequences in translation

Maria C. Sterrett,
Lauryn A. Cureton,
Lauren N. Cohen
et al.

Abstract: The RNA exosome is an evolutionarily conserved exoribonuclease complex that consists of a 3-subunit cap, a 6-subunit barrel-shaped core, and a catalytic base subunit. Missense mutations in genes encoding structural subunits of the RNA exosome cause a growing family of diseases with diverse pathologies, collectively termed RNA exosomopathies. The disease symptoms vary and can manifest as neurological defects or developmental disorders. The diversity of the RNA exosomopathy pathologies suggests that the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…As 3’-end trimming of the 7S pre-rRNA to the mature 5.8S required to assemble functional ribosomes by the RNA exosome is one of the best defined function of this complex, defects in this process would be predicted to alter translation. Indeed, a recent study demonstrated that several different budding yeast models of exosomopathies impair translation albeit, there appear to be differences in how translation is affected in different yeast models of exosomopathies (29). The analysis of the core subunit here is consistent with the previous finding (29), suggesting that mutations that affect the core subunits vs the cap subunits of the RNA exosome cause distinct translational defects with defects in core subunits such as Rrp41 causing an overall reduction of ribosomes while defects in cap subunits leading to formation of halfmers indicating a potential problem in 60S maturation or subunit joining.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As 3’-end trimming of the 7S pre-rRNA to the mature 5.8S required to assemble functional ribosomes by the RNA exosome is one of the best defined function of this complex, defects in this process would be predicted to alter translation. Indeed, a recent study demonstrated that several different budding yeast models of exosomopathies impair translation albeit, there appear to be differences in how translation is affected in different yeast models of exosomopathies (29). The analysis of the core subunit here is consistent with the previous finding (29), suggesting that mutations that affect the core subunits vs the cap subunits of the RNA exosome cause distinct translational defects with defects in core subunits such as Rrp41 causing an overall reduction of ribosomes while defects in cap subunits leading to formation of halfmers indicating a potential problem in 60S maturation or subunit joining.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study demonstrated that several different budding yeast models of exosomopathies impair translation albeit, there appear to be differences in how translation is affected in different yeast models of exosomopathies (29). The analysis of the core subunit here is consistent with the previous finding (29), suggesting that mutations that affect the core subunits vs the cap subunits of the RNA exosome cause distinct translational defects with defects in core subunits such as Rrp41 causing an overall reduction of ribosomes while defects in cap subunits leading to formation of halfmers indicating a potential problem in 60S maturation or subunit joining. Further studies will be required to determine whether these changes in translation are confirmed in patient cells or mammalian disease models as well as how these molecular changes alter the proteome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation